The Star, 10 Disember 2007 (Star Publications (Malaysia) Berhad, 2007)
Indian have achieved progress in various fields over the lass 50 years, although more need to be done to make them competitive in the face of globalisation , said MIC president Datuk Seri S.Samy Vellu.